Optimization of machining processes by using criteria of maximum productivity and minimum cost - Aead, M. Ahmed (Universiti Malaysia Perlis (UniMAP), 2014)
In manufacturing, the machining process by using norms of the maximum productivity and minimum cost is knotted. In many cases, the increase of machining modes leads to an increase in productivity, and the machining cost also increases. The present thesis formulates a set of mathematical models that enable the setting of maximum productivity and minimum cost parameters on machine tools. Three new mathematical approaches have been developed to achieve this objective. In the first approach, maximum productivity is given as a function of the increase of cutting speed at (x) time equal 0.93. The second approach focuses on optimizing multi tool machining process with simultaneous actions. Here, the maximum productivity at (k) factor, which is 1.28 of changing the cutting speed, has been derived. Whereas in the third approach, maximum productivity and minimum cost for single and multi tools are presented. The equations are useful in modeling and predicting the processing mode that will give maximum productivity and minimum cost. By keying in the developed mathematical expressions in MATLAB, the productivity of the machine tool is calculated. This work has been carried out under dry conditions. The results give the optimum cutting speed (Vopt) at maximum productivity for a single cutting tool for high speed steel and carbide as a theoretical. Whereas by keying a diameter of work piece is 25mm, depth of cut 2mm and feed rate 0.21mm/rev, which are achieved experimentally, the proper cutting speed for HSS of the tested materials is 50 m/min. whereas the optimum cutting speeds of cutting tool machining process of the different materials as a theoretical of maximum productivity for cemented carbide is 95 m/min. whilst for the multi cutting tool of the same materials the maximum theoretical productivity is obtained at 80 m/min. whereas the optimum cutting speeds for the multi cutting tool machining process of the same materials as an experimental for maximum productivity at 75 m/min. However, increasing the machining regimes leads to an increase in both of machining cost and productivity. In the minimum cost approach, which is a proper cutting speed of the tested materials is 46 m/min. The convenient range values of multi-cutting speed for both productivity and cost obtained in this work is 40 to 90m/min, and a favorable range of cutting speed is 40 to 60 m/min to get the minimum cost. The appropriate range of cutting speed of the mathematical model for the productivity for single and multi -cutting tool for intermediate hardness of work piece material is 35 to 69 m/min, 50 to 90m/min, respectively. Although both theoretical and experimental data sets show similar behavior, there are slight deviations within acceptable range for the two data set values.